2019
DOI: 10.1080/13632752.2019.1582746
|View full text |Cite
|
Sign up to set email alerts
|

Turning points in a qualitatively different social space: young adults’ reflections of alternative provision

Abstract: young people who attend Alternative Provision settings report positive relationships and experiences of learning. There is however very little research which explores the longer term outcomes of attending this sort of provision. Retrospective life history interviews were undertaken with 18 young adults in their early to mid-20s who had attended Alternative Provision in England. Interviews focused on schooling, exclusion, attending Alternative Provision and the impact of this on what they had done since leaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…It is important to note that the quality of PRU provision can be highly varied (Smith, 2019). Whilst these positive experiences from PRUs are consistent with findings elsewhere (Berridge et al, 2021;Malcolm, 2019;Smith, 2019) there were still negative aspects of the provision. This included the limited amount of resources available for PRU staff, and the reduced curriculum offer, which limited the academic options available to the pupils.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…It is important to note that the quality of PRU provision can be highly varied (Smith, 2019). Whilst these positive experiences from PRUs are consistent with findings elsewhere (Berridge et al, 2021;Malcolm, 2019;Smith, 2019) there were still negative aspects of the provision. This included the limited amount of resources available for PRU staff, and the reduced curriculum offer, which limited the academic options available to the pupils.…”
Section: Discussionsupporting
confidence: 74%
“…There have been negative perceptions of PRUs historically, with terms such as 'dumping grounds' and 'last resort' schools used to describe them (Solomon, 2011). Despite this view, research often highlights the positive experiences of young people in these settings, where supportive and caring relationships are formed between young people and staff (Berridge et al, 2021;Malcolm, 2019;Smith, 2019). These supportive relationships can help learners to grow in confidence as part of a positive turning point (Malcolm, 2019), improving both their social and academic skills (Smith, 2019).…”
Section: School Exclusions and Prusmentioning
confidence: 99%
See 2 more Smart Citations
“…Narrative research has been the main way to explore the trajectories of students who were at risk of exclusion (Burton & Vicente, 2021;Stolz, 2021). Looking at the objectives and taking into account that we are going to explore the different events and experiences that certain students have gone through throughout their life course, the ideal method to achieve the stated objectives would be that of life histories (Juliá, 2018;Malcolm, 2019). Denzin and Bertaux (in Bolívar et al, 2001, p. 29) indicated that life history is the "elaboration (by biographers or researchers) as a case study of the life of a person/s or institution, which may take various forms of elaboration and analysis" using life stories or other methods of enquiry into the lives of subjects.…”
Section: Methodsmentioning
confidence: 99%